Leptomonas seymouri: Adaptations to the Dixenous Life Cycle Analyzed by Genome Sequencing, Transcriptome Profiling and Co-infection with Leishmania donovani - Kraeva, Natalya; Butenko, Anzhelika; Hlaváčová, Jana; Kostygov, Alexei; Myškova, Jitka; Grybchuk, Danyil; Leštinová, Tereza; Votýpka, Jan; Volf, Petr; Opperdoes, Fred; Flegontov, Pavel; Lukeš, Julius; et al. (PLoS pathogens, 2015)
The co-infection cases involving dixenous Leishmania spp. (mostly of the L. donovani complex) and presumably monoxenous trypanosomatids in immunocompromised mammalian hosts including humans are well documented. The main opportunistic parasite has been identified as Leptomonas seymouri of the sub-family Leishmaniinae. The molecular mechanisms allowing a parasite of insects to withstand elevated temperature and substantially different conditions of vertebrate tissues are not understood. Here we demonstrate that L. seymouri is well adapted for the environment of the warm-blooded host. We sequenced the genome and compared the whole transcriptome profiles of this species cultivated at low and high temperatures (mimicking the vector and the vertebrate host, respectively) and identified genes and pathways differentially expressed under these experimental conditions. Moreover, Leptomonas seymouri was found to persist for several days in two species of Phlebotomus spp. implicated in Leishmania donovani transmission. Despite of all these adaptations, L. seymouri remains a predominantly monoxenous species not capable of infecting vertebrate cells under normal conditions.
Keywords: Coinfection; fyziologická adaptace; Polymerase Chain Reaction; infekce prvoky kmene Euglenozoa; polymerázová řetězová reakce; Leishmania donovani; Euglenozoa Infections; Animals; leishmanióza viscerální; stanovení celkové genové exprese; stadia vývoje; koinfekce; Trypanosomatina; Genes, Protozoan; modely nemocí na zvířatech; Life Cycle Stages; Leishmaniasis, Visceral; zvířata; protozoální geny; Psychodidae; Gene Expression Profiling; Transcriptome; transkriptom; Disease Models, Animal; Adaptation, Physiological